2021
DOI: 10.12688/wellcomeopenres.16801.2
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin and cefixime combination versus azithromycin alone for the out-patient treatment of clinically suspected or confirmed uncomplicated typhoid fever in South Asia: a randomised controlled trial protocol

Abstract: Background: Typhoid and paratyphoid fever (enteric fever) is a common cause of non-specific febrile infection in adults and children presenting to health care facilities in low resource settings such as the South Asia.  A 7-day course of a single oral antimicrobial such as ciprofloxacin, cefixime, or azithromycin is commonly used for its treatment. Increasing antimicrobial resistance threatens the effectiveness of these treatment choices. We hypothesize that combined treatment with azithromycin (active mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…One AMU policy that could be modified is to increase the dose of ciprofloxacin given, to achieve a “mutant prevention concentration”, although this has not shown promise in the limited empirical studies carried out thus far (Fantin et al 2009). Another antimicrobial usage policy that could be considered is a switch to combination therapy for suspected typhoid fever (Zmora et al 2018; Giri et al 2021), although without improved diagnostics this might just serve to increase the overall antibiotic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…One AMU policy that could be modified is to increase the dose of ciprofloxacin given, to achieve a “mutant prevention concentration”, although this has not shown promise in the limited empirical studies carried out thus far (Fantin et al 2009). Another antimicrobial usage policy that could be considered is a switch to combination therapy for suspected typhoid fever (Zmora et al 2018; Giri et al 2021), although without improved diagnostics this might just serve to increase the overall antibiotic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…This supports Current study observation that the combination therapy does not significantly enhance the effectiveness of treatment compared to Meropenem alone. Contrastingly, a study by Giri. et al (2021) reported that the combination of Azithromycin with other antibiotics led to a quicker resolution of symptoms and a shorter hospital stay (22).…”
Section: Discussionmentioning
confidence: 84%
“…Contrastingly, a study by Giri. et al (2021) reported that the combination of Azithromycin with other antibiotics led to a quicker resolution of symptoms and a shorter hospital stay (22). Their findings suggested that Azithromycin could play a vital role in enhancing the effectiveness of the treatment for enteric fever (23,24).…”
Section: Discussionmentioning
confidence: 84%
“…6 A Phase IV, international, multicentre randomised controlled trial is currently in progress in South Asia evaluating this combination. 7…”
mentioning
confidence: 99%